E-Commerce System - Gawsan R.; T.W.M.I.P.S. Bandara; W.P.G.M.Weerasinghe; S.R. Kulasekara; D. I. De Silva; Thisuri Dias (International Journal of Engineering and Management Research, 2022)
This paper presents the development of an E-commerce System (ECS) for users. ECS is able to manage the details of users who have registered to the system. Not only that but also this system can manage order details that are user has ordered. In addition, this system provides calculation service payment for items that are in the cart. The users of ECS are the customer and the admin. This system was developed using the MERN stack and MongoDB as the database platform.